Analysis of D-dimer Levels in Deep Vein Thrombosis Patients - Anton Triyadi; Rachmawati A. Muhiddin; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
It is reported the incidence of DVT is approximately 84 cases per 100,000 each year, with 30-50% of untreated DVT are at risk for pulmonary embolism, causing a 12% increase in mortality rate. An accurate and rapid diagnosis of DVT is needed to minimize the risk of complications and prevent unnecessary anticoagulant therapy without waiting for the results of a diagnostic examination using ultrasound. This study aimed to determine the diagnostic value of plasma D-dimer levels on Doppler ultrasound for DVT diagnosis to help clinicians to select a rapid and accurate diagnostic test for DVT diagnosis. This research was a retrospective study using data from medical records and performed at the Medical Record Installation of Dr. Wahidin Sudirohusodo Hospital, Makassar, by taking data on patients with DVT along with the results of D-dimer and Doppler ultrasound from January to December 2018. D-dimer levels were measured using an immunoturbidimetric method with a reference value of<0.5 Î¼g/mL. A total of 33 samples were obtained with a mean of D-dimer value was higher in positive Doppler (5.29) compared to negative (2.31), although not statistically significant (p> 0.05). Also, the mean of Wells score was higher in positive Doppler (4.74) compared to negative (4.17), although not statistically significant (p> 0.05). The diagnostic values of D-dimer were as follows: sensitivity of 92.6%, specificity of 33.3%, positive predictive value of 86.2%, negative predictive value of 50.0%, and accuracy of 81.8%. D-dimer test can be used both for screening and diagnostic tests with cut-off value â‰¥ 2 Î¼g/mL.